From fangs to antidotes: A scoping review on snakebite burden, species, and antivenoms in the Eastern Mediterranean Region. - Ali Alshalah; David J Williams; Alessandra Ferrario (PLoS Neglected Tropical Diseases)
Background Snake bites cause considerable morbidity and mortality worldwide, yet evidence from low- and middle-income countries remains fragmented. This is particularly the case in Eastern Mediterranean Region where available data on snake bites is relatively weak. Without reliable data, it is difficult to make the case for greater visibility and investment to address the snakebite burden in this Region. A scoping review was therefore conducted to summarize evidence on snake bites in countries of the Eastern Mediterranean. Methodology/principal findings The review employed manual and electronic searching methods of four databases plus Google Scholar, ultimately including 196 records from 20 countries published between 2000 and 2023. More than half originated from Iran, Morocco, and Pakistan. Many records lacked information on permanent sequalae, disability, snake species, and types and sources of antivenoms. When identified, offending snakes belonged to 30 species. Use of more than 12 types of antivenoms were described across the Region, and some were not specific to indigenous species. Conclusion/significance Despite the relatively large number of publications identified, the data were concentrated in just a few countries in the Region, and there was little or no information available for the remainder. As is the case worldwide, disability associated with snake bites was poorly characterized and quantified across the Region. There is an urgent need for concrete action at national and regional levels to enhance epidemiological surveillance, research, and the collection of clinical, disability and outcomes data to inform policy and public health investment. Greater regional cooperation and collaboration is also crucial for addressing this neglected disease throughout the Region.